Tinjauan Akuntansi Syariah Dalam Penggunaan Sistem Informasi Akuntansi Multi-Level Marketing Pada E-Commerce Indonesia - Zaini Nur Aini; Lantip Susilowati (LPPM ISNJ Bengkalis, 2022)
Islamic accounting is a financial recording procedure that generates information from an accounting information system (AIS) and forms a continuous cycle of repeat business policies. This study aims to describe the views of Islamic accounting related to AIS used for e-commerce-based multi-level marketing (MLM) businesses, as well as confirm the MLM law. The method used in this research is an entirely content analysis method. This research understands the flow of written sources, and then it is linked on an ongoing basis. The results showed that using AIS in the MLM business in e-commerce is permissible. It can be considered valid if the process still follows sharia. Fair according to sura An-Nahl (16) verse 90. It can be accounted for following sura Al-Baqarah (2) verse 282. This research can be a reference and consideration in using AIS in MLM business that stays away from the prohibition of muamalah.